Thomas Johnson: the publisher as an agent of Enlightenment. - Rybczak, Emil (Dutch Crossing, 2021)
This article discusses the varied business practices of the eighteenth-century publisher Thomas Johnson. It develops our understanding of the Enlightenment, as experienced by its participants and as a historical phenomenon, by cataloguing Johnson's creation and exploitation of communications and retail networks. His significant contribution to the publication of French works, held alongside his facilitation of Scottish engagement with the Republic of Letters, demonstrates the falsity of Jonathan Israel's thesis that the Enlightenment was fundamentally divided between moderate and radical camps. Anne Goldgar's work emphasises the importance of communication in defining the Enlightenment as a participatory community. Siskin and Warner characterise the Enlightenment as the material forms such communication took. Exploration of publishers' status within this community, and their significance in controlling the means by which its ideas were disseminated, reveals their power in mediating who could participate in the Enlightenment, and the direction of its development.